2013
DOI: 10.2106/jbjs.l.01730
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose rhBMP-2 for Adults: Major and Minor Complications

Abstract: This is the largest study of which we are aware that examines complications associated with high-dose rhBMP-2. Major surgical complications occurred in 11.6% of patients, and 11.6% experienced major medical complications. There was a cancer prevalence of 3.4%, but no correlation between increasing rhBMP-2 dosage and cancer, radiculopathy (seen in 1% of the patients), or seroma (seen in 0.6%) was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
61
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 44 publications
0
61
0
Order By: Relevance
“…Recent studies showed that the off-label use of a high dose (more than 40 mg) of rhBMP-2 was associated with an increased risk of new cancer. We should therefore, further evaluate the potential risk of cancers in patients receiving high-dose rhBMP2 [31], [32].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that the off-label use of a high dose (more than 40 mg) of rhBMP-2 was associated with an increased risk of new cancer. We should therefore, further evaluate the potential risk of cancers in patients receiving high-dose rhBMP2 [31], [32].…”
Section: Discussionmentioning
confidence: 99%
“…While attempts to identify optimal formulations and methods of delivery are ongoing, the use of BMP-2 in spine surgery remains controversial due to reports of safety issues. 1,3,7,9,11,12,14,16,17,19 Although the basic mechanisms underlying BMP-2-induced vertebral fusion and heterotopic ossification are largely understood, [4][5][6]13,15 the parameters for optimal imaging of these complications are still being identified.…”
Section: Discussionmentioning
confidence: 99%
“…46 Despite the positive results achieved with the use of rhBMPs in spine fusion, some serious negative fi ndings have recently emerged concerning the lack of clinical evidence of the advantage of rhBMP-2 over bone grafts and its possible link with important cancer risks. [47][48][49][50][51] For this reason, the authors of this article considered the combination of osteoinductive and osteoconductive materials such as DBM as a valid alternative to autologous/homologous bone, thus perhaps overcoming the limitation of current therapeutic strategies. 30 , 32 ,52,53 DBM is available in various formulations produced by numerous manufacturers, containing varying amounts of osteogenic factors.…”
Section: ➢ Key Pointsmentioning
confidence: 99%